2014
DOI: 10.1139/cjce-2013-0587
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of anti-icing operations for snow and ice control of parking lots and sidewalks

Abstract: This paper describes an empirical study aimed at investigating the performance of the anti-icing strategy for snow and ice control of parking lots and sidewalks. The research is motivated by the need to address several key questions concerning various operational decisions related to the anti-icing strategy, including its relative effectiveness under different weather and site conditions, treatment options, and optimal application rates. Extensive field tests were conducted under traffic controlled environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Ice accumulation is not only a concern for drivers, but also the cause for personal injuries on walkways due to numerous slipping and falling. [1][2][3][4][5][6][7][8][9][10][11][12][13] When ice accumulates on the wings of aircraft, turbine engine structures, or insulators and transmission lines on power systems, it will impose serious problems and cause some disastrous damage in the aircraft and power industry. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] In the winter of 2008-2009, frozen rain lasted for more than three weeks in Hunan and Jiangxi provinces, causing downfall of 37% of Ice accumulation poses a series of severe issues in daily life.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ice accumulation is not only a concern for drivers, but also the cause for personal injuries on walkways due to numerous slipping and falling. [1][2][3][4][5][6][7][8][9][10][11][12][13] When ice accumulates on the wings of aircraft, turbine engine structures, or insulators and transmission lines on power systems, it will impose serious problems and cause some disastrous damage in the aircraft and power industry. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] In the winter of 2008-2009, frozen rain lasted for more than three weeks in Hunan and Jiangxi provinces, causing downfall of 37% of Ice accumulation poses a series of severe issues in daily life.…”
Section: Introductionmentioning
confidence: 99%
“…Ice accumulating on solid surfaces can cause serious problems on roads, aircrafts, power lines, ships, and some energy equipment. Statistics indicates that 10–15% of roadway accidents are related to weather conditions, which have caused thousands of human injuries and deaths and millions of dollars in property damage annually.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Canada, a study conducted by researchers at the University of Waterloo [14] concluded that salt gradation has great impact on the performance of the de-icing salt. A comparative study was conducted between coarse road salt with average particle size of almost 6.5 mm (the majority of the material being in the range of 4 to 9 mm); and fine road salt with average particle size of 4.3 mm (the majority of the material within the range of 1.6 to 7 mm); and another road salt (referred to as UW salt) with average particle size of 2.5 mm (the majority of the material <5 mm).…”
Section: Coarse Grained Saltmentioning
confidence: 99%
“…Compared to solid salt, brine was found to be more effective when the mass amount of salt (NaCl) used was considered in test sites treated by solid salt and brine under similar winter events (Hossain et al 2014). In practise, spreading of saturated brine takes effect immediately if there is frost or ice on the road, whereas dry or prewetted salt takes time to become effective (Fonnesbech 2001).…”
Section: Introductionmentioning
confidence: 99%